2017
DOI: 10.1186/s13613-017-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high flow in management of children with status asthmaticus: a retrospective observational study

Abstract: BackgroundAsthma is the most common obstructive airway disease in children and adults. Nasal high flow (NHF) is a recent device that is now used as a primary support for respiratory distress. Several studies have reported use of NHF as a respiratory support in status asthmaticus; however, there are no data to recommend such practice. We therefore conducted this preliminary study to evaluate NHF therapy for children with status asthmaticus admitted to our PICU in order to prepare a multicentre randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 49 publications
2
67
0
5
Order By: Relevance
“…Previous in vitro and in vivo studies on aerosol delivery via HFNC all utilized unit dose with a single concentration . With unit dose administration, the inhaled dose was 10% to 15% in similar pediatric models, which was consistent with our findings using unit dose delivery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous in vitro and in vivo studies on aerosol delivery via HFNC all utilized unit dose with a single concentration . With unit dose administration, the inhaled dose was 10% to 15% in similar pediatric models, which was consistent with our findings using unit dose delivery.…”
Section: Discussionsupporting
confidence: 89%
“…However, asthmatic patients might benefit more from effective bronchodilator delivery than the 20% improvement on work of breathing benefited from a higher flow rate. Baudin et al summarized their success in using an intermittent unit dose of albuterol via HFNC for severely asthmatic patients might be due to the relatively low gas flow rate (1 L/kg/min) utilized in their study . Thus decreasing flow to achieve efficient bronchodilator delivery might be a viable strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when patients need extended periods of aerosol administration, use of mask or mouthpiece is complicated by decreased patient comfort and tolerance. In‐line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years . The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC .…”
Section: Introductionmentioning
confidence: 99%
“…In-line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years. 8,9,[11][12][13] The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC. 14 Pediatric patients were reported to be more comfortable and less anxious after inhaling aerosol bronchodilator via HFNC, 8,9 which has also shown the potential benefits of avoiding intubation in a group of pediatric asthma patients, 26% of whom already had acidosis at PICU admission.…”
mentioning
confidence: 99%
See 1 more Smart Citation